Chapter 1 Rethinking our Assumptions about Moral Status - Clarke, Steve (Oxford University Press, 2021)
Recent technological developments and potential technological developments of the near future require us to try to think clearly about what it is to have moral status and about when and why we should attribute moral status to beings and entities. What should we say about the moral status of human non-human chimeras, human brain organoids, artificial intelligence, cyborgs, post-humans, and human minds that have been uploaded into a computer, or onto the internet? In this introductory chapter we survey some key assumptions ordinarily made about moral status that may require rethinking. These include the assumptions that all humans who are not severely cognitively impaired have equal moral status, that possession of the sophisticated cognitive capacities typical of human adults is necessary for full moral status, that only humans can have full moral status, and that there can be no beings with higher moral status than ordinary adult humans. We also need to consider how we should treat beings and entities when we find ourselves uncertain about their moral status.